Dakwah Islam dalam Dunia Pendidikan Bahasa Arab untuk Membentuk Generasi Muslim yang Sadar: Al-Da’wah al-Islāmiyyah fī Majāl Ta’līm al-Lugah al-‘Arabiyyah litakwīn Jaili al-Muslim al-Wa’ī - Amelia, Siti Sarah; Burhanuddin, Burhanuddin (Study Program of Arabic Language Teaching, 2023)
This research aims to investigate the positive impact of using Arabic in an educational context on understanding the Islamic values contained in it. The target of this research is students from the Faculty of Da'wah and Communication Sciences at UIN Syarif Hidayatullah Jakarta. This research applies a qualitative approach using case study and questionnaire techniques as the main method of data collection. From the survei results, it can be concluded that the majority of respondents (90%) consider it important to include Arabic in the university curriculum. The reason for implementing the use of Arabic is because it involves moral development, cross-cultural communication, and understanding Islamic teachings. Respondents also saw the benefits of learning Arabic in the context of deepening understanding of the Koran, improving the quality of worship, and forming polite character. Overall, the survei supports the success of Arabic in making a positive contribution to the moral and spiritual formation of students. Some respondents had different points of view because they found it difficult to learn Arabic, but they provided several different solutions for learning it. The next reason for differences of opinion is the status of Arabic as an international language because not all universities have muslim students.